PENGARUH STRESS KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA TERMINAL TIPE A PONDOK CABE - Savira Yustika Fahayyina; Aden Prawiro Sudarso (CV. KAMPUSA AKADEMIK PUBLISING, 2026)
This study aims to determine the effect of work stress and work environment on employee performance at Terminal Type A Pondok Cabe. The research method used is quantitative with a descriptive approach. The population in this study consisted of 65 employees, and the sampling technique applied was saturated sampling, so all members of the population were included as the sample. Data were collected through questionnaires using a Likert scale and analyzed using multiple linear regression assisted by SPSS version 25.The results showed that partially, work stress (X1) had a positive and significant effect on employee performance with a t-value of 4.241 > t-table 1.669 and a significance value of 0.000 < 0.05. The work environment (X2) also had a positive and significant effect on employee performance with a t-value of 7.152 > t-table 1.669 and a significance value of 0.000 < 0.05. Simultaneously, work stress and work environment had a positive and significant effect on employee performance with an R value of 0.703, indicating a strong relationship among variables. The coefficient of determination (R²) of 0.495 shows that 49.5% of employee performance is influenced by work stress and work environment, while the remaining 50.5% is influenced by other factors outside this study.